Energy leakage analysis of the radar and communication integrated waveform. Issue 3 (1st May 2018) - Chen, Xingbo; Liu, Zhipeng; Liu, Yiming; Wang, Zhaowei
Abstract : When minimum shift keying (MSK)'s carrier is changed as the linear frequency modulation (LFM) signal, it is called as MSK‐LFM for short. It is a new type of the radar‐communication multifunctional integrated waveform. Under the assumption that the bandwidth of the radar receiver is equal to that of the LFM signal, the energy leakage of MSK‐LFM is analysed. The trade‐off between the number of modulated bits and the energy leakage is derived analytically. The derived equation demonstrates that the relationship between the radar detection performance and digital communication performance of MSK‐LFM, which also gives the principle of designing the integrated waveform. To better ensure the radar detection performance, a method is proposed to reduce the energy leakage at the expense of sacrificing certain communication capacity.